2016
DOI: 10.1111/1753-0407.12366
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and clinical characteristics of patients with type 1 diabetes mellitus: A multicenter registry study in Guangdong, China

Abstract: The adult-onset form of T1D is not rare in China. The registry participants were characterized by older age at onset, lower BMI, and a higher prevalence of DKA at onset compared with those in regions with a high incidence of T1D, such as northern Europe. These findings contribute to a better understanding of the heterogeneity of T1D in different populations and so will help healthcare providers to develop management models that are more suitable for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 33 publications
2
23
1
Order By: Relevance
“…The inclusion criteria and detailed protocol were described in our previous studies. 18 The study protocols were approved by the ethics committee of the Third Affiliated Hospital of Sun Yat-sen University. All adult participants provided written informed consent.…”
Section: Participantsmentioning
confidence: 99%
“…The inclusion criteria and detailed protocol were described in our previous studies. 18 The study protocols were approved by the ethics committee of the Third Affiliated Hospital of Sun Yat-sen University. All adult participants provided written informed consent.…”
Section: Participantsmentioning
confidence: 99%
“…7 8 Our previous study also indicated that the onset of type 1 diabetes in adulthood is not rare in China. 9 Yet little is known about its incidence in adults aged more than 20 years. 10 …”
Section: Introductionmentioning
confidence: 99%
“…The Guangdong Type 1 Diabetes Mellitus translational study (GTT study) was a prospective multicentre hospital-based register study, conducted in 16 tertiary hospitals throughout 12 cities of Guangdong, China. The inclusive criteria and detailed protocols have been reported previously [8,9]. Newly diagnosed and priorly diagnosed patients with T1DM who visited the participating hospitals consecutively from June 2011 to July 2018 and finished at least one-year follow-up were enrolled in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Those who were compatible with the last two criteria but had the duration of the disease before the start of insulin treatment for more than one to two weeks were highly suspected and also assigned into the FT1DM group. Typical type 1 diabetes was defined as follows [8]:…”
Section: Methodsmentioning
confidence: 99%